What tuberculosis can teach us about combating multidrug-resistant Gram negative bacilli. (May 2016) - Banerjee, Ritu; Starke, Jeffrey R.
Abstract: There are striking similarities between the dual pandemics of multidrug-resistant tuberculosis (MDR TB) and multidrug-resistant Gram negative bacilli (MDR GNB) despite fundamental differences in the pathogenesis and epidemiology of these pathogens. In this perspective, we highlight several strategies that have been used by the global TB community to address the MDR TB problem, including approaches to: encourage appropriate use of anti-TB medications, enhance appropriate utilization of molecular diagnostic testing, facilitate development of new antimicrobial agents, and strengthen surveillance systems and infection control practices. Understanding the successes and challenges of these strategies for MDR TB control will be instructive for efforts to curb emergence and spread of MDR GNB.